Evolution of Private Returns to Tertiary Education during Transition: Evidence from Slovenia - Tjaša Bartolj; Aleš Ahčan; Aljoša Feldin; Sašo Polanec (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2012)
This paper analyzes the evolution of private returns to tertiary education during the period of transition from a socialist to a market economy using the personal income tax data of all Slovenian workers employed between 1994 and 2008. We document a rich interplay between supply and demand in the labor markets of high school and university graduates. We show that, in spite of signi cant increases in the labor supply, the demand for university graduates dominated and increased the rates of return in the early period of transition (1994-2001), while in the later period (2001-2008) the opposite was the case. We also provide evidence on considerable heterogeneity in the rates of return between genders, levels, and elds of study, with particularly large (low) returns to the elds that were suppressed (favored) during socialism. These initial di erences in returns have, however, gradually declined.
Keywords: J24; 330; Returns to Education; Tertiary Education; Fields of Study; Mincerian Regressions